LITERASI DIGITAL UPAYA PENCEGAHAN KENAKALAN REMAJA DI ERA TEKNOLOGI - Tunjung Bayu Sinta; Hanifah Hanifah; Harjanti Harjanti (Jurnal Pengabdian Masyarakat Sabangka, 2026)
The rapid development of digital technology has a significant impact on adolescent behavior, including the emergence of various forms of juvenile delinquency in cyberspace. In 2024, the Indonesian Child Protection Commission (KPAI) recorded 41 cases of children becoming victims of pornography and cybercrime, with the most reports related to sexual crimes and bullying in digital media. This community service activity was carried out at SMP Negeri 1 Tasikmadu Karanganyar, targeting seventh-grade students through providing socialization on digital literacy and efforts to prevent juvenile delinquency in the technological era. The activity began with a pretest and ended with a posttest. The expected outcome of this community service activity is to instill an understanding among adolescents about efforts to prevent juvenile delinquency in the technological era.